Outcomes of trabecular metal total ankle replacement: a longitudinal observational cohort study of 239 consecutive cases from the Swedish Ankle Registry - Anders Henricson; Alexandra Undén; Åke Carlsson; Lars Jehpsson; Björn Rosengren (Acta Orthopaedica, 2022)
Background and purpose: Information on outcomes after some modern total ankle replacement (TAR) designs is scarce. We therefore examined outcomes after trabecular metal (TM) TAR in Sweden by use of data from the national registry. Patients and methods: On December 31, 2020, 239 primary TM TARs had been reported to the Swedish Ankle Registry. We analyzed prosthesis survival probability, using exchange or permanent extraction of components as endpoint for 239 protheses with mean follow-up of 2.2 years (0.1–6.6), risk of revision, as well as patient-reported outcome measures (SEFAS/EQ-5D/EQ-VAS) and satisfaction with surgery. Results: 7/239 prostheses (3%) had been revised by December 31, 2020. We found an overall prosthesis survival probability of 95% (95% CI 89–98) after 3 years. 2 years after surgery 81% of the answering patients were satisfied or very satisfied with surgery and patients reported median SEFAS 36 (max 48), EQ-5D 0.90 (max 1), and EQ-VAS 80 (max 100). Interpretation: We found short- to mid-term outcomes after TM TAR to be at least as good as after other TAR designs regarding prosthesis survival and patient-reported satisfaction.